Predicted and validated theoretical results for stellarators in the frame of eurofusion WPS2 - Castejón, F. (Вопросы атомной науки и техники, 2018)
The main results of the work performed under EUROfusion for stellarator optimization are shown. Physics and engineering activities are undertaken in order that both are considered from the very beginning and the physics optimization takes into account the engineering constrains. are considered The HELIAS (W7-X like) configuration has been chosen as starting point and the physics criteria comprises minimization of NC transport, reduction of bootstrap current in order to have a feasible island-based divertor, reduction of turbulence and improving MHD stability and fast ion confinement. Coils are also simplified and breeding blanket studies together with the power balance of the device.